2020
DOI: 10.1037/tra0000574
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of NR3C1 and FKBP5 is associated with posttraumatic stress disorder, posttraumatic growth, and resilience.

Abstract: Objective: Understandings of the biological mechanisms underpinning posttrauma responses are limited. This pilot study aimed to expand research in this area by examining the relationship between DNA methylation of stress genes nuclear receptor subfamily 3 group C member 1 (NR3C1) and FK06 binding protein 5 (FKBP5) with an array of posttrauma responses of posttraumatic stress disorder (PTSD) symptom severity, posttraumatic growth (PTG), and resilience. Method: First-year paramedicine students (N ϭ 47) completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
(60 reference statements)
1
15
0
1
Order By: Relevance
“…Interestingly, in our study FKBP5 bin 2 methylation correlated with symptom severity, especially anxiety, as well as inversely with empathic perspective taking. This is consistent with previous reports showing increased FKBP5 methylation being associated with high levels of anxiety, depression and PTSD symptoms [ 31 , 54 , 57 ] (for review see [ 49 ]). Our findings expand on this indicating that FKBP5 methylation is also linked to empathy, which is compatible with studies demonstrating that emotional empathy is negatively affected by the experience of acute stress [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in our study FKBP5 bin 2 methylation correlated with symptom severity, especially anxiety, as well as inversely with empathic perspective taking. This is consistent with previous reports showing increased FKBP5 methylation being associated with high levels of anxiety, depression and PTSD symptoms [ 31 , 54 , 57 ] (for review see [ 49 ]). Our findings expand on this indicating that FKBP5 methylation is also linked to empathy, which is compatible with studies demonstrating that emotional empathy is negatively affected by the experience of acute stress [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, there are now multiple sources of objective evidence for PTG as a construct including self-report, qualitative, and longitudinal studies (Tedeschi et al, 2018). Emerging research has also found evidence for epigenetic markers of PTG (Miller et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another SNP (rs3800374 T allele frequency~18%) is associated with an increased cortisol response in males following psychosocial stress (Mahon et al, 2013). A recent study identified epigenetic modifications in FKBP5 and NR3C1 that appear to impact PTSD severity (Miller et al, 2020). Polymorphisms within regulators of the HPA axis have also been identified, including the CRH receptor 1 (CRHR1 Gen-Bank NG_009902.1), that have roles in modulating sensitivity to GCs.…”
Section: The Hpa Axis: a Moderator Of Health And Diseasementioning
confidence: 99%